Retrospective analysis of the prevalence of specialised palliative care services for patients with metastatic breast cancer. Issue 5 (18th September 2020) - Jäger, Eva Maria; Filipits, Martin; Glechner, Anna; Zwickl-Traxler, Elisabeth; Schmoranzer, Gabriele; Pecherstorfer, Martin; Kreye, Gudrun
Abstract : Background: Patients with metastatic breast cancer (MBC) have a considerable symptom burden and may require extensive care for a long period of time. Palliative care (PC) has the potential to improve their quality of care and reduce their use of medical services. However, the role of specialised PC (SPC) in patients with MBC remains unclear. Patients and methods: We performed a retrospective analysis of the medical records of patients diagnosed with breast cancer (BC) from 2008 to 2018 at an university-based referral centre to examine the extent of early and late integration of SPC services for patients with MBC. A descriptive analysis of the patients was also established. Results: In all, 932 patients were diagnosed with BC from 2008 to 2018; 225 of these patients had or developed metastases related to their BC. In addition, 132 patients received SPC (58.7%) and 93 patients did not receive SPC (41.3%). The median probability of overall survival (OS) for patients who did not receive SPC services was 3.6 years (95% CI 2.0 to 5.1) and 1.8 years (95% CI 1.3 to 2.3) (p<0.0001) for patients who did receive SPC. In multivariate analysis, referral to SPC services was independently associated with OS (HR 1.60, 95% CI 1.16 to 2.22, p=0.004). Conclusion: Patients who received SPC lived significantly shorter amounts of time than patients not referred for SPC services at our hospital. We concluded that the referral to SPC services was often too late and should be implemented earlier in the course of the disease. We suggest that patients with MBC should participate in a consultation by a SPC team ≤60 days after the start of systemic palliative anticancer therapy in addition to endocrine treatment. Larger prospective studies are needed to evaluate the benefit of the early integration of SPC services for patients with MBC.